Characteristics of patients (expatriates and long-term travellers) with suspected malaria, being evacuated by fixed-wing air ambulances out of Sub-Saharan Africa to Johannesburg, South Africa. a retrospective case review, for the period July 2006 through June 2009 - Van der Walt, Renske (My University, 2012)
Background Promotion of job opportunities and tourism in African countries has led to an increase in expatriates in malaria endemic areas. A paucity of data exist on characteristics and numbers of expatriates and long-term travellers being evacuated from sub-Saharan Africa for suspected malaria infections diagnosed while still in Africa. Methods A retrospective flight record review of a South African fixed-wing air-ambulance provider from June 2006 through July 2009 was performed. Adult expatriates and long-term travellers with suspected malaria being evacuated from sub-Saharan African countries to Johannesburg, South Africa were included. Results Suspected malaria was the single most common diagnosis for dispatching airambulances with 81 (11.9%) of the 679 flights. Accuracy of the initial diagnosis, based on confirmation of malaria at the receiving facility was 78.4% for blood smears, 92.3% for rapid detection tests and 42.8% for clinical signs alone. P. falciparum (alone, or in combination with other Plasmodium species) was the most frequently isolated species at both the referring (100%) and receiving (88.2%) facilities in cases where the species was documented. The suspected malaria patients were predominantly male 69 (84.1%), with a mean age of 42.1 ±12.8 years, and were in sub-Saharan Africa for occupational reasons 65 (79.3%). Angola, the Democratic Republic of Congo and Mozambique were the countries of origin in 48 (58.5%) of the suspected malaria flights. Compliance on appropriate malaria chemoprophylaxis was documented in two (2.4%) suspected malaria patients. Intubation as a marker of severity was required for 15 (18.3%) patients, and one (1.2%) patient died inflight. No statistically significant difference (p=0.50) was shown for intubation requirements when comparing patients who had utilised malaria chemoprophylaxis with the patients who had not utilised chemoprophylaxis. Conclusions Patients presented in advanced stages of severe/complicated malaria with concurrent poor chemoprophylaxis utilisation and compliance. Appropriate chemoprophylaxis did not decrease the severity of presentation (based on intubation requirements) and did not guarantee complete malaria protection.
Keywords: Malaria; Emergency Medical Services; Plasmodium falciparum